Metallothioneins are neuroprotective agents in lysosomal storage disorders. Issue 2 (15th February 2018) - Cavalca, Eleonora; Cesani, Martina; Gifford, Jennifer C.; Sena-Esteves, Miguel; Terreni, Maria Rosa; Leoncini, Giuseppe; Peviani, Marco; Biffi, Alessandra
Abstract : Objective: Lysosomal storage disorders (LSDs) are a broad class of inherited metabolic diseases caused by the defective activity of lysosomal enzymes. Central nervous system (CNS) manifestations are present in roughly 50% of LSD patients and represent an unmet medical need for them. We explored the therapeutic potential of metallothioneins (MTs), a newly identified family of proteins with reported neuroprotective roles, in the murine models of two LSDs with CNS involvement. Methods: MT‐1 overexpressing transgenic mice (MTtg) were crossed with the murine models of Batten and Krabbe diseases. Changes in the survival and manifestations of the disease in the MTtg setting were assessed. In addition, we analyzed the therapeutic effects of MT‐1 CNS gene delivery in one of these LSD models. Results: Constitutive expression of MT‐1 exerted favorable phenotypic effects in both LSD models. MT‐LSD mice showed a 5% to 10% increase in survival and slower disease progression as compared to not‐transgenic LSD mice. Rescue of Purkinje cells from degeneration and apoptosis was also observed in the MT‐LSD models. This phenotypic amelioration was accompanied by a modulation of the disease‐associated activated inflammatory microglia phenotype, and by a reduction of oxidative stress. Importantly, for the clinical translation of our findings, the very same effects were obtained when MTs were delivered to brains by systemic AAV gene transfer. Interpretation: MTs can be considered novel therapeutic agents (and targets) in LSDs and potentiate the effects of approaches aiming at correction of the disease‐causing enzyme deficiency in the CNS. Ann Neurol 2018;83:418–432 Ann Neurol 2018;83:418–432